Ultimate Shear Load Capacity of Cross-sectional Curved Steel Webs. Issue 2 (3rd April 2021) - Van Staen, Gilles; Fang, Heng; Van Bogaert, Philippe; De Backer, Hans
Abstract: Various types of curved steel plates are commonly used in aerospace, naval and bridge engineering. Either very thin plates are used in order to create lightweight structures or thicker plates in order to prevent stability problems. In the last decades, curved steel panels have been used along the bridge direction and on a cross-sectional level. A practical case is discussed and used to determine the model characteristics for an intensive numerical parameter study. Plates with different curvatures and thicknesses are investigated. Aspect ratios of one and two are considered, together with two sets of edge conditions. The edge conditions and material model are verified by experimental tests of flat plate girders. An imperfection sensitive study is performed in order to find the ultimate load of the curved plates. Two mode shapes are considered, categorized as stable and unstable. Results show that the geometric imperfection shape affects the load–deflection path, but not the ultimate load capacity, for slender curved plates. For plates with a higher curvature or lower slenderness ratio b/t, an unstable mode seems to have a disadvantageous influence on the ultimate load. Finally, a design method for curved plates with rigid vertical stiffeners is proposed.